Collaborative Governance in the Tourist Alley Innovation of Makassar City - Deasy Mauliana; Nurman Sahar; Rusman Siddiki; Haedar Akib (Jurnal Ilmiah Ilmu Administrasi Publik, 2023)
The needs of the community in terms of public services have increased, so the government as a public service agency is trying to respond to all the community's needs in terms of public services. This condition is caused by the development of the global environment, which affects public services and demands the government to play a role in addressing various community interests. In implementing public services, the government cannot work alone. Cooperation or collaboration from various parties outside the government agency is needed as an effort in the government's response as a public servant to improve public services that meet what is needed by the community. The research method used in this study is a descriptive qualitative method. Data is obtained based on interview results, observation results, and a review of documents related to the research to describe and analyze phenomena and events individually or in groups. Data collection techniques are conducted through interviews, observations, documentation. In this research, the description/characteristics of informants consist of four (4) main elements, namely: Government element: Tourism Office, and Tallo District, Business/Practitioners: MSMEs, Academics: Lecturers involved in the implementation of Tourism Alley, Community: Community implemented for approximately one year in the city of Makassar, South Sulawesi Province. The selection of the study locus considers collaboration between sectors in improving public service innovation. The research result of collaborative governance on the innovation of tourism alley in Makassar city is that the collaboration that has been done in the tourism alley of Makassar city has been quite good, but still needs to be improved, especially the involvement of various stakeholders.